Library Carpentry: Towards a New Professional Dimension (Part II – Automatic Authority Control to Enhance Retrieval) - Mukhopadhyay, Parthasarathi; Mukhopadhyay, Mondrita (Journal of Information and Knowledge, 2021)
Authority control for bibliographic data management in Indian libraries is generally a neglected area and thereby library OPACs of the country (including OPAC of the National Library) supports only the finding function of a catalogue and not the collocating function. In this context, the part II of the three part series on library carpentry (part I has been published in April issue) is an attempt to apply library carpentry methods in building authority datasets from scratch. It deals with the methodologies for developing authority datasets by applying data wrangling techniques and subsequent transformations of these datasets into ready-to-import MARC 21 format (for authority data). Like the previous part of the series, this research study is also represented through a case study. The case study narrates development of geographic name authority datasets for - states and union territories (level I), districts of India (level II), sub-districts (level III) and community development blocks of India (level IV). It also demonstrates that how the merged geographic name authority file for India can be implemented in an open source ILS and can become instrumental in enhancing retrieval efficiency through geodetic search feature in an open source library discovery system. It concludes that the proposed mechanisms and methodology (supported with proofs of the concept) may lead to a new era of authority-controlled cataloguing in Indian libraries.